Effects of soil type and farm management on soil ecological functional genes and microbial activities - Reeve, Jennifer R; Schadt, Christopher W; Carpenter-Boggs, Lynne; Kang, Sanghoon; Zhou, Jizhong; Reganold, John P (The ISME Journal, 2010)
Relationships between soil microbial diversity and soil function are the subject of much debate. Process-level analyses have shown that microbial function varies with soil type and responds to soil management. However, such measurements cannot determine the role of community structure and diversity in soil function. The goal of this study was to investigate the role of gene frequency and diversity, measured by microarray analysis, on soil processes. The study was conducted in an agro-ecosystem characterized by contrasting management practices and soil types. Eight pairs of adjacent commercial organic and conventional strawberry fields were matched for soil type, strawberry variety, and all other environmental conditions. Soil physical, chemical and biological analyses were conducted including functional gene microarrays (FGA). Soil physical and chemical characteristics were primarily determined by soil textural type (coarse vs fine-textured), but biological and FGA measures were more influenced by management (organic vs conventional). Organically managed soils consistently showed greater functional activity as well as FGA signal intensity (SI) and diversity. Overall FGA SI and diversity were correlated to total soil microbial biomass. Functional gene group SI and/or diversity were correlated to related soil chemical and biological measures such as microbial biomass, cellulose, dehydrogenase, ammonium and sulfur. Management was the dominant determinant of soil biology as measured by microbial gene frequency and diversity, which paralleled measured microbial processes.